Evaluation of Taxonomic Characteristics of Matlo and Phala Bat Rabies-Related Lyssaviruses Identified in South Africa - Viljoen, Natalie; Weyer, Jacqueline; Coertse, Jessica; Markotter, Wanda (Viruses, 2023)
We report the genetic characterization of two potentially novel rabies-related lyssaviruses identified from bats in Limpopo province, South Africa. Matlo bat lyssavirus (MBLV) was identified in two Miniopterus natalensis (Natal long-fingered) bats in 2015 and 2016, and Phala bat lyssavirus (PBLV) was identified in a Nycticeinops schlieffeni (Schlieffen’s) bat in 2021. The distribution of both of these bat species is largely confined to parts of Africa, with limited reports from the Arabian Peninsula. MBLV and PBLV were demonstrated to group with the unassigned and phylogroup I lyssaviruses, respectively. MBLV was most closely related to Lyssavirus caucasicus (WCBV), whereas PBLV was most closely related to Lyssavirus formosa (TWBLV-1) and Taiwan bat lyssavirus 2 (TWBLV-2), based on analysis of the N and G genes, the concatenated N + P + M + G + L coding sequence, and the complete genome sequence. Based on our analysis, MBLV and WCBV appeared to constitute a phylogroup separate from Lyssavirus lleida (LLEBV) and Lyssavirus ikoma (IKOV). Analysis of the antigenic sites suggests that PBLV will likely be serologically distinguishable from established lyssaviruses in virus-neutralization tests, whereas MBLV appeared to be antigenically highly similar to WCBV. Taken together, the findings suggested that, while PBLV is likely a new lyssavirus species, MBLV is likely related to WCBV.